Development of a novel polyethylene glycol-corticosteroid-conjugate with an acid-cleavable linker - Funk, Dorothee; Schrenk, Hans-Hermann; Frei, Eva (Journal of drug targeting, 2011)
Background: Corticosteroids like dexamethasone are often used in the treatment of inflammatory diseases. Despite efficacy, their use is limited by severe side-effects. Targeted drug-delivery to the site of inflammation would be advantageous for the patients. Macromolecules can be used for this approach, because they accumulate at sites of inflammation due to the enhanced permeability and retention effect.Purpose: Our aim was to develop a polymer-corticosteroid-conjugate for the treatment of inflammatory diseases. The authors covalently linked a derivative of dexamethasone to the macromolecule polyethylene glycol (PEG), using an acid-cleavable linker to achieve lysosomal drug-release.Methods: The corticosteroid-PEG-conjugate was synthesized and characterized by nuclear magnetic resonance spectroscopy (NMR) and mass spectrometry. Cleavage experiments were performed to study the nature of products after incubation at acidic pH, and the efficacy of the conjugate was tested in two model cell lines.Results: Acid hydrolysis of the novel corticosteroid-PEG-conjugate resulted in two new derivatives of dexamethasone. The conjugate was effective in both model cell lines showing lysosomal release and efficacy of the cleavage products.Discussion and conclusion: The authors new corticosteroid-PEG-conjugate shows glucocorticoid activity and should be developed further to treat inflammatory diseases with reduced side-effects while retaining drug efficacy.